IS1245 genotypic analysis of Mycobacterium avium isolates from patients in Brazil - Saad, Maria Helena (1999)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Hanseníase. Rio de Janeiro, RJ, Brasil.